2020
DOI: 10.1101/2020.08.24.261008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell intercalation driven by SMAD3 underlies secondary neural tube formation

Abstract: Body axis elongation is a hallmark of the vertebrate embryo, involving the architectural remodelling of the tailbud. Although it is clear how bi-potential neuro-mesodermal progenitors (NMPs) contribute to embryo elongation, the dynamic events that lead to de novo lumen formation and that culminate in the formation of a 3-Dimensional, secondary neural tube from NMPs, are poorly understood. Here, we used in vivo imaging of the chicken embryo to show that cell intercalation downstream of TGF-beta/SMAD3 signalling… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The first heterogeneity that we have observed is patterned spatially in a gradient along the antero-posteriorly axis (Sox2 high anteriorly, Bra high posteriorly) in the dorsal part of the region. This graded expression has been described in chicken embryo (22)(49) and is coherent with fate maps studies at earlier stages showing that the antero-posterior axis of the epiblast/streak gives rise to progeny along the medio-lateral axis (4,6). For instance, anterior cells expressing high levels of Sox2 can give rise to neural cells and more posterior cells expressing high levels of Bra to PSM (and eventually to lateral mesoderm to cells located even more caudally).…”
Section: Discussionsupporting
confidence: 84%
“…The first heterogeneity that we have observed is patterned spatially in a gradient along the antero-posteriorly axis (Sox2 high anteriorly, Bra high posteriorly) in the dorsal part of the region. This graded expression has been described in chicken embryo (22)(49) and is coherent with fate maps studies at earlier stages showing that the antero-posterior axis of the epiblast/streak gives rise to progeny along the medio-lateral axis (4,6). For instance, anterior cells expressing high levels of Sox2 can give rise to neural cells and more posterior cells expressing high levels of Bra to PSM (and eventually to lateral mesoderm to cells located even more caudally).…”
Section: Discussionsupporting
confidence: 84%
“…Although a role for Sox2 in the control of progenitor cell migration has, to our knowledge, not previously been reported, recent works have demonstrated that a rise of Sox2 expression promotes the transition of posterior progenitors to NT during chick embryo secondary neurulation ( Kawachi et al, 2020 ) and that turning off Sox2 is necessary for NMP to enter the mesoderm in zebrafish embryo ( Kinney et al, 2020 ). In addition, it has also been observed by time-lapse analysis that the dorsal zone between the PZ and the NT does not display excessive cell migration but rather local cell intercalations ( Roszko et al, 2007 ; Gonzalez-Gobartt et al, 2021a ). Taken together, these data confirm the hypothesis that Sox2 High cells could be laid down as the PZ moves posteriorly.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies show that SMAD3 drives cell intercalation underlies secondary neural tube formation in the mouse embryo (Gonzalez-Gobartt et al, 2021). Moreover, it was known that the BMP-Rho-ROCK1 pathway targets MLC to control actin remodeling in fibroblasts (Konstantinidis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%